2021
DOI: 10.1002/smll.202104626
|View full text |Cite
|
Sign up to set email alerts
|

Bone Tumor Suppression in Rabbits by Hyperthermia below the Clinical Safety Limit Using Aligned Magnetic Bone Cement

Abstract: composition [14,19] of MNPs. For example, we obtained an SLP of 3417 W metal g 1 − at a field of 33 kA m −1 and 380 kHz in Co 0.03 Mn 0.27 Fe 2.7 O 4 /SiO 2 MNPs. [14] In recent years, great progress has been made on in vivo magnetic hyperthermia treatments of solid tumors. [20][21][22][23][24][25][26][27] It was reported that tumors in mice can be eliminated after receiving magnetic hyperthermia treatment using coreshell MNPs. [6] Systemically delivered ZnMn-ferrite MNPs were shown to have increased the intra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
(125 reference statements)
0
6
0
Order By: Relevance
“…This could be obtained by tuning the cation distribution in the spinel structure of magnetite/maghemite NPs or by doping NPs with Mn or Zn to decrease its anisotropy. Indeed, Mn-ferrite and Zn-doped iron oxide nanomaterials have shown interesting in vivo performance under clinical conditions, while MnZn-ferrite NPs also show promising applications. ,, …”
Section: Resultsmentioning
confidence: 99%
“…This could be obtained by tuning the cation distribution in the spinel structure of magnetite/maghemite NPs or by doping NPs with Mn or Zn to decrease its anisotropy. Indeed, Mn-ferrite and Zn-doped iron oxide nanomaterials have shown interesting in vivo performance under clinical conditions, while MnZn-ferrite NPs also show promising applications. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The main difference between such an environment and an aqueous solution is that the motion of NPs is prohibited, leading to much lower heating capabilities than that Small 2022, 18, 2205037 in a solution where NPs are free to move and align in the AC field. [23] In our ex vivo experiments, 50 µL NP aqueous solution with a concentration of 2.7 mg mL −1 was injected into the dorsal muscle of mice (dosage of 6.75 mg kg −1 , comparable to that used for MRI and much lower than typically used for hyperthermia). While the effective NP concentration in the body is difficult to quantify, it is expected to be much smaller than the original concentration of the solution as the NPs diffuse rapidly after subcutaneous injection.…”
Section: Resultsmentioning
confidence: 99%
“…[4,[20][21][22] Our previous work suggests that Zn-doped ferrites (Zn 0.3 Fe 2.7 O 4 ) exhibited higher specific loss power (SLP) than Fe 3 O 4 owing to their higher magnetization. [20,23,24] Co addition, on the other hand, can increase the magnetic anisotropy, which can enhance the SLP at higher fields. [20] Recent trends exploring the potential of combining MHT and PTT to produce cumulative local heating can bring about high heating efficiency in hyperthermia therapy.…”
mentioning
confidence: 99%
“…This effect is probably due to the differences in the orientations of the total field in the two cases, as explained for the immobilized samples. This observation might have practical applications as both in vivo and in vitro, the recent experimental data have shown that the pre-alignment of MNPs during the cellular uptake [ 25 ] or in a bone cement, [ 64 ] significantly enhances the MH efficiency when the AMF was applied along the direction of the alignment. Our results suggest that the superposition of a perpendicular static DC field during MH might significantly increase the heat released, as compared to the parallel configuration.…”
Section: Resultsmentioning
confidence: 99%